Code Authorship and Fault-proneness of Open-Source Android Applications : An Empirical Study - Businge, John; Kawuma, Simon; Bainomugisha, Engineer (International Conference on Predictive Models and Data Analytics in Software Engineering, 2020)
Context: In recent years, many research studies have shown how human factors play a significant role in the quality of software components. Code authorship metrics have been introduced to establish a chain of responsibility and simplify management when assigning tasks in large and distributed software development teams. Researchers have investigated the relationship between code authorship metrics and fault occurrences in software systems. However, we have observed that these studies have only been carried on large software systems having hundreds to thousands of contributors. In our preliminary investigations on Android applications that are considered to be relatively small, we observed that applications systems are not totally owned by a single developer (as one could expect) and that cases of no clear authorship also exist like in large systems. To this end, we do believe that the Android applications could face the same challenges faced by large software systems and could also benefit from such studies. Goal: We investigate the extent to which the findings obtained on large software systems applies to Android applications. Approach: Building on the designs of previous studies, we analyze 278 Android applications carefully selected from GitHub. We extract code authorship metrics from the applications and examine the relationship between code authorship metrics and faults using statistical modeling. Results: Our analyses confirm most of the previous findings, i.e., Android applications with higher levels of code authorship among contributors experience fewer faults.
Keywords: Software faults; Minor Contributors; Major Contributors; Most Values Contributors; Total Contributors